VxLAN Application in Cloud Datacenter Network - Jiexin Zhang; Zhiren Fu; Zhiming Wu; Wenhua Xu; Haifeng Xu (Dianxin kexue)
Cloud datacenter demand on new techniques and new architecture were summarized firstly. And also the mainstreams of VxLAN technical schemes were analyzed. Then typical VxLAN applications in cloud datacenter network were studied. Finally, several VxLAN problems were discussed in case of scale applications in cloud datacenter.